Study of ionospheric irregularities from Kolhapur (16.4°N, 74.2°E). (April 2018) - Sharma, A.K.; Chavan, G.A.; Gaikwad, H.P.; Gurav, O.B.; Nade, D.P.; Nikte, S.S.; Ghodpage, R.N.; Patil, P.T.
Abstract: The paper reports night time observations of ionospheric irregularities made through amplitude scintillation of 251 MHz signal at Kolhapur (16.4°N, 74.2°E), an equatorial Appleton anomaly region using spaced antenna system. Monthly and night time percentage of occurrence of scintillations, during increasing solar cycle from January 2011 to August 2015, is discussed. The parameters such as-maximum cross-correlation function (C I ), Fade Rate are also studied. The percentage occurrence is observed to be higher in post sunset period and during equinoctial months than in winter and summer months. Scintillation occurrence is observed to be suppressed during increasing solar activity.C I shows seasonal changes. Percentage of occurrence ofC I  ≥ 0.5 decreases with increase in solar activity and fade rate also shows solar activity dependence. Highlights: In this article amplitude scintillation data of January 2011 to August 2015 has been analyzed. This period is the ascending phase of solar cycle. Night time and seasonal observations of scintillation index, fade rate and cross correlation function has been analyzed. Suppression of percentage of occurrence of strong scintillation has been observed during solar maximum.